Заметка о манере повествования в Житии протопопа Аввакума (A note on the narration in archpriest Avvakum’s Life ) - Egeberg, Erik (Poljarnyj vestnik, 2010)
This short paper comments on the marked oral quality of archpriest Avvakum's prose, focusing on cases where the author pretends to have forgotten a name and then suddenly recollects it.
Keywords: archpriest Avvakum; archpriest Avvakum's life